Maternal & Child Health Nursing : care of the childbearing & childrearing family - Pillitteri, Adele (Philadelphia : Wolters Kluwer, 2014)
Adele Pillitteri aims to ensure that today's students have a technical understanding, without losing the importance of compassion in their role as a nurse. The text presents pediatrics and maternity as a continuum of knowledge, taking a holistic approach and viewing maternity and pediatric content as a family event. The text links theory closely with application that helps students gain a deeper understanding of content and be better prepared to practice in their careers."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Maternal -- Child nursing; Family health; Holistic nursing